IMPLEMENTASI HYBRID LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAN 2 MALANG - Faridatul Kibtiyah Zaini; Anwar Sa’dullah; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This article describes the implementation of hybrid learning in learning Islamic religious education at SMAN 2 Malang. This research is motivated by how a student carries out a learning process that takes place online or offline using a hybrid learning system. The hybrid learning system had been implemented by SMAN 2 Malang before the pandemic period, so that during the pandemic the system was even more intensified. The type of research used by the researcher in this research is a case study. And the results of the data obtained from the data are descriptive qualitative, namely in the form of words, images and not in the form of numbers. In collecting data, researchers used techniques including observation, interviews, and documentation. Meanwhile, in analyzing the data, the researcher uses data collection techniques, data reduction, and data presentation. In checking the validity of the data, researchers used source triangulation and method triangulation. The results of this study are the lesson plans used in accordance with the current lesson plans, the learning time used is only 30 minutes per JP, the application used E-Learning, the teaching materials used are textbooks, the method used is lectures, exercises, evaluations by providing final assignment to students.